Local and Systemic Antibody Responses in Humans with Helicobacter pylori Infection - Thomas G Blanchard; John G Nedrud; Steven J Czinn (Canadian Journal of Gastroenterology)
Immunization can prevent or cure an otherwise chronic helicobacter infection in several animal models despite the chronic nature of natural helicobacter infections. Differences in the antigenic specificity of the antibodies may contribute to the protection observed in these experimental animals. The goal of the present study was to compare the local and systemic antibody responses of humans with chronic Helicobacter pylori infection with those of an individual with spontaneous resolution of infection to find an immunological correlate of protection. Spontaneous resolution of infection was accompanied by a change in immunoblot profiles. Whereas a broad range of H pylori antigens was recognized in chronically infected patients (including the patient who ultimately cleared the infection spontaneously), resolution of infection in the absence of therapeutic agents resulted in the recognition of only several immunodominant antigens. The most dominant antigen was approximately 66 kDa in molecular mass. Immunoblot analysis demonstrated that these antibodies were specific for the structural subunits of the urease enzyme. These studies suggest that the success of antihelicobacter immunization may be due to the ability of vaccination to induce an immune response against antigens that are normally not immunodominant during the course of infection.